Design Rules for Template‐Confined DNA‐Mediated Nanoparticle Assembly. Issue 44 (24th September 2018) - Zhou, Wenjie; Lin, Qing‐Yuan; Mason, Jarad A.; Dravid, Vinayak P.; Mirkin, Chad A.
Abstract: Template‐based strategies are becoming increasingly important for controlling the position of nanoparticle‐based (NP‐based) structures on surfaces for a wide variety of encoding and device fabrication strategies. Thus, there is an increasing need to understand the behavior of NPs in confined spaces. Herein, a systematic investigation of the diffusion and adsorption properties of DNA‐modified NPs is presented in lithographically defined, high‐aspect‐ratio pores using a template‐confined, DNA‐mediated assembly. Leveraging the sequence‐specific binding affinity of DNA, it is discovered that although NP adsorption in deep polymer pores follows a traditional Langmuir adsorption model when under thermodynamic control, such NPs kinetically follow Fick's classical law of diffusion. Importantly, these observations allow one to establish design rules for template‐confined, DNA‐mediated NP assembly on substrates based on pore dimensions, NP size and shape, NP concentration, temperature, and time. As a proof‐of‐concept example, these design rules are used to engineer a vertical, four‐layer assembly consisting of individual octahedral NPs stacked on top of one another, with in‐plane positioning defined by pores generated by e‐beam lithography. Abstract : A systematic investigation of the diffusion and adsorption properties of DNA‐functionalized nanoparticles (NPs) in high‐aspect‐ratio pores is carried out using a template‐confined, DNA‐mediated assembly. Design rules are subsequently established based on observations where NPs with variant sizes and shapes can be assembled into 3D structures in high precision with high yield.